Impact of the use of training programs for mixed martial arts qualified fighters with different fighting styles on the efficiency of competitive activity - Kozina, Z.; Pustomelnik, O.; Boychuk, Y.; Kozin, O.; Sobko, I.; Polishchuk, S.; Shyyan, O. (Journal of Physical Education and Sport, 2025)
Background and purpose. Mixed martial arts (MMA) require a high level of technique, tactics, strategy and cognitive activity. A stable complex of the manifestation of all these capabilities forms a fighting style unique to each fighter. Purpose: to develop and substantiate a system of differentiated training of MMA fighters with different fighting styles. Material and methods. The study involved 42 qualified MMA fighters. Athletes were randomly divided into control and experimental groups of 21 athletes each. The training program of MMA fighters of the control group in the annual cycle was identical for all athletes. In the experimental group, the training program was different for representatives of different fighting styles. The effectiveness of the developed system of differentiated training of MMA fighters with different fighting styles was assessed based on the results of all-Ukrainian competitions. Results. It was determined that the use of the system of differentiated training of athletes depending on the fighting style had a positive effect on their competitive efficiency. The control and experimental groups, which did not differ before the experiment, had significant differences after the experiment. Conclusion. A significant increase in the coefficient of competitive efficiency was observed in MMA fighters of the experimental group. At the same time, these changes are not significant in the control group. It is recommended to use the training system developed by us for fighters of different fighting styles based on fighting styles.